2012
DOI: 10.3109/00952990.2012.668597
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Alexithymia in Alcohol-Dependent Patients Does Not Influence Outcomes after Inpatient Treatment

Abstract: Multimethod alexithymia assessments with an observer scale have been advised to judge the relationship with resulting outcome in CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…The mean TAS-20 score for the psychiatric sample was consistent with previous research (de Haan, Schellekens, et al, 2012;Meganck, Vanheule, Inslegers, & Desmet, 2009) and similar to the mean TAS-20 score reported in a Canadian psychiatric sample (Frewen et al, 2008). The mean TAS-20 score for the community sample was similar to the mean TAS-20 scores reported in a large Canadian community sample (Parker et al, 2003) and two Australian community samples (Gignac, Palmer, & Stough, 2007;Parry, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The mean TAS-20 score for the psychiatric sample was consistent with previous research (de Haan, Schellekens, et al, 2012;Meganck, Vanheule, Inslegers, & Desmet, 2009) and similar to the mean TAS-20 score reported in a Canadian psychiatric sample (Frewen et al, 2008). The mean TAS-20 score for the community sample was similar to the mean TAS-20 scores reported in a large Canadian community sample (Parker et al, 2003) and two Australian community samples (Gignac, Palmer, & Stough, 2007;Parry, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Alexithymia may also predict treatment engagement, in terms of session attendance and working alliance (drug-dependent outpatients who were higher in alexithymia attended fewer sessions and formed weaker alliances) (Cleland et al, 2005 ). In studies on inpatients with alcohol use disorder (de Haan et al, 2012b ), baseline alexithymia showed no relation to abstinence, time in treatment or changes in disorder severity at 1-year follow-up. Similarly, as concerns SUDs (de Haan et al, 2011 ), alexithymia (measured as both a continuous and a categorical variable) was not related to abstinence, and high-scoring alexithymics did not differ from low-scoring alexithymics in mean time in treatment or dropout rates (50 vs. 43%).…”
Section: Theoretical Backgroundmentioning
confidence: 89%
“…In a study involving a cohort of 100 individuals with alcohol-use disorders, no effects of alexithymia were seen on treatment outcome, as indicated by self-reports of use 30 days after cessation of an inpatient treatment program that consisted of a combination of motivational interviewing (MI) and CBT approaches delivered in group therapy [55]. Nonetheless, the preponderance of data suggests that alexithymia warrants consideration in treatment development efforts for addictions.…”
Section: Implications For Substance-abuse Treatmentmentioning
confidence: 99%